Lactobacillus Reuteri DSM 17938 in Infantile Colic: A Systematic Review and Meta-Analysis - Burhannudin Ichsan; Nining Lestari; Sulistyani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Infantile colic, defined as paroxysmal, excessive, and consolable crying without an identifiable cause. It is common in the first 3 months of life. There have been many RCT studies conducted. A systematic synthesis is required to summarize the results of these RCTs. This study was aimed to systematically analyze the benefits of Lactobacillus reuteri DSM 17938 for infantile colic. Methods. This systematic review and meta-analysis used keywords: (“infantile colic” OR “abdominal cramps” OR “abdominal cramp” OR “infant colic”) AND “lactobacillus reuteri” AND (placebo OR placebos) AND (“randomized controlled trial” OR RCT). The databases used were: pubmed, science direct, and google scholar. Meta-analysis was conducted to combine the articles. The eligibility criteria were: patient with infantile colic, intervention with L. reuteri DSM 17938, control was placebo, RCT study design, outcome with dichotomous scale, all races, all ethnicities, all countries, all genders, in English, and not limited by year. Results. The search resulted in 800 articles. After reducing duplication, the number of articles was 747. Screening with titles and abstracts resulted in 13 full teks articles. Six articles fitted the eligibility criteria. The results of the meta-analysis were as follows. The forest plot showed that the combined effect of the six articles showed an RR of 0.47 and was statistically significant (p <0.001). Conclusion. Based on the results of this meta-analysis, L. reuteri DSM 17938 is recommended for infants with infantile colic. There were no significant side effects with the use of L. reuteri DSM 17938 on infantile colic.